Commercial banks in Iraq had applied in practice different forms of its activities upon surplus funds that deposited from individual, firms and many governments units - علي ابراهيم محمد (Journal of Economics and Administrative Sciences, 2011)
These deposits take many forms like current acc, deposits in order to growth and serve national economy Various in varicose perspectives . The problem of this paper its concern with un applied the mathematical models that used in profitability analysis of current acc , and deposits in view of risk, profit efficiency and financial leverage for this reason the paper discussion use the cumulate mathematical model to solve these problem, that content three variables that be used to measuring profitability by consequent replacement method by stable base and by moving base for 2007 – 2009 applied the data collect from Iraq middle east bank.